Prevalence of malnutrition and its associated factors among under five children at debretabor town north-west ethiopia - Hwot Yisak; Amien Ewunetei (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Background: An estimated of 230 million under-five children are believed to be chronically malnourished in developing countries Similarly, about 54% of deaths among children of this age group are believed to be associated with malnutrition in developing countries. In Sub-Saharan Africa, 41% of under-five children are malnourished and deaths from malnutrition are increasing on daily basis in the region. Malnutrition continues to be a major public health problem in developing countries. It is the most important risk factor for the burden of disease causing about 300, 000 deaths per year directly and indirectly responsible for more than half of all deaths in children. So to minimize these direct or indirect causes of death additional investigation is needed since there is shortage of evidences. Objective: To assess prevalence of malnutrition among children of age 6-59 months in Debre Tabor town, North-West Ethiopia in December 2019 . Methods: A community based cross sectional study was conducted. The study area is Debre Tabour Town which is located North-West of Ethiopia, and is 97Km away from Bahir Dar. The sample size of the study was 277. Data were collected using structured questionnaire and anthropometric measurements. After the completion of data collection; editing, coding and cleaning was carried out. The data was analyzed manually. Different frequency tables, graphs and descriptive summaries were used to describe the study variables. Chi-square test and 95% CI were computed to measure the presence of the association between the outcome and the explanatory variables. P-value <0.05 was considered as a statistical significant. Result: The prevalence of stunting, underweight and wasting was 23.2%, 11.9%, 7.6% respectively. About 1.8% of the children had acute malnutrition. Variables like family size, income, maternal and paternal educational status, diarrhea, health status during pregnancy, ANC visit were highly significant (associated) with chronic malnutrition (stunting) at P-value <0.005. Conclusion and recommendation: Based on the findings of this study we can conclude that; child malnutrition is still high in the study area even though it is lower than the national and regional EDHS 2016 national report. I recommend that nutritional education should be given by health extension workers to improve feeding and hygiene practice at HH level. There should be safe and adequate water supply, Immunization to overcome malnutrition in long term.